PENGARUH KONDISI PENGGORENGAN TERHADAP KUALITAS ROTAN MANAU (CALAMUS MANAN MIQ.) - Osly Rachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
The effect of cooking condition on the quality of rattan is presented in this article. Round fresh manau rattan samples, each of 100 cm in length and 3 cm in diameter were 80 stems in all.The samples were devided into 4 groups before cooking. Each group was cooked with four different oil mixtures and four levels of cooking time.The results reveal that the composition of cooking oils has a significant effect on the cane color and compressive strength parallel to grain. but has no effect on shear strength of the rattan.The mixtures containing coconut oil tends to reduce the rate of rattan skin color change during cooking. Also, such composition produced better rattan skin color in comparison with those treated with others.